2000
DOI: 10.1007/s003300050059
|View full text |Cite
|
Sign up to set email alerts
|

Improved mammographic interpretation of masses using computer-aided diagnosis

Abstract: The aim of this study was to evaluate the effectiveness of computerized image enhancement, to investigate criteria for discriminating benign from malignant mammographic findings by computer-aided diagnosis (CAD), and to test the role of quantitative analysis in improving the accuracy of interpretation of mass lesions. Forty sequential mammographically detected mass lesions referred for biopsy were digitized at high resolution for computerized evaluation. A prototype CAD system which included image enhancement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…The current study did not compare to most other studies which used different protocols [9,14,20,21,24,27,28], examining lesions of a limited size or structure (due to limitations of the CAD systems used, e.g. [9]) or using pre-selected or pre-scanned cases [27].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The current study did not compare to most other studies which used different protocols [9,14,20,21,24,27,28], examining lesions of a limited size or structure (due to limitations of the CAD systems used, e.g. [9]) or using pre-selected or pre-scanned cases [27].…”
Section: Discussionmentioning
confidence: 96%
“…The quality of such systems depends critically on the tumour detection rate and the number of falsepositive (FP) marks per image. Both sensitivity and FP marks per image have already been well investigated for the ªImageCheckerº system (R2, Los Altos, Calif.) [12,13,14]. The sensitivity data varies between 59 and 87 %, depending on the case selection criteria and the definition of true positive (TP) used [12,13,15,16,17]; however, to date, no studies, have assessed the sensitivity and FP marks per image for the newly available ªSec-ond Lookº CAD system (CADx Medical Systems, Quebec, Canada).…”
mentioning
confidence: 99%
“…There are also substantial differences between our Bayesian network and other computer-assisted diagnosis systems that use suspicious cases selected from biopsy databases to train their systems (24,25,27,30,31,34,46,47). Our Bayesian network, in contrast, was trained on consecutively collected mammographic findings, perhaps allowing it to more accurately estimate posttest probabilities and better balance improvements in sensitivity and specificity with more realistic estimates of breast cancer prevalence.…”
Section: Breast Imaging: Computer Model To Classify Mammographic Findmentioning
confidence: 99%
“…In fact, it has been suggested that the suboptimal performance indicates that computer-assisted detection may have unanticipated negative effects on radiologist decision making, perhaps by deferring recall when marks are not present (22,23). Several groups have improved classification of mammographic abnormalities (computerassisted diagnosis) with computer-extracted imaging features (24)(25)(26) or with radiologist-observed features (27)(28)(29)(30)(31) in selected biopsy cases. We aim to extend this research by developing a Bayesian network that uses radiologistobserved features found in the American College of Radiology National Mammography Database (NMD) format (32,33).…”
mentioning
confidence: 99%
“…Today's computer-aided technologies, medical imaging, modern design and manufacturing have further assisted in those advances and created new possibilities in the development of tissue engineering. Such possibilities include, for example, using noninvasive computed tomography (CT) or magnetic resonance imaging (MRI) techniques to generate tissue structural views for 3-D anatomical model, for tissue classification and trauma/tumor identification [24][25][26][27][28][29][30][31][32][33], using computer-aided design/computer-aided manufacturing (CAD/CAM) and rapid prototyping (RP) technology to fabricate the physical models of hard tissues, tissue scaffolds, and the custom-made tissue implant prostheses [34][35][36][37][38][39][40][41][42], and applying the anatomical and physical modeling for reconstructive surgeons and tissue implementation [43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%